Efficacy of virtual reality in pediatric burn patients: a systematic review and meta-analysis - Yang, Zhengbing; Yang, Hao; Wang, Zhuxu; Liu, Song (Frontiers in Virtual Reality, 2025)
ObjectivesBurn care procedures cause significant pain and anxiety in children, often hindering recovery and rehabilitation. Virtual reality (VR) distraction therapy offers a promising non-pharmacological approach. This meta-analysis synthesizes evidence on the efficacy of VR compared to standard care for pediatric burn patients.MethodsWe systematically searched PubMed, Embase, Cochrane Library, and Web of Science for randomized controlled trials (RCTs) evaluating VR distraction during burn care procedures in children. Standard care was the comparator. Primary outcomes included pain intensity and anxiety. Secondary outcomes included physiological distress (heart rate), procedural time, and functional improvement (active range of motion - ROM). Data were pooled using random-effects models, calculating standardized mean differences (SMDs) or mean differences (MDs) with 95% confidence intervals (CIs). Risk of bias was assessed using the Cochrane RoB 2 tool.ResultsSixteen RCTs met inclusion criteria. Meta-analysis demonstrated statistically significant benefits favoring VR: VR significantly reduced procedural pain (SMD = −0.92, 95% CI: −1.21 to −0.63; p < 0.001), indicating a large effect. VR significantly reduced procedural anxiety (SMD = −1.05, 95% CI: −1.42 to −0.68; p < 0.001), indicating a large effect. Lower physiological arousal during procedures with VR (MD = −8.72 bpm, 95% CI: −12.35 to −5.09, p < 0.001). VR interventions were associated with significantly shorter procedure durations compared to standard care (MD = −3.24 min, 95% CI: −5.01 to −1.47; p < 0.001). VR significantly improved active ROM during rehabilitation sessions (SMD = 0.76, 95% CI: 0.41 to 1.11; p < 0.001), indicating a moderate-to-large effect.ConclusionFindings from this study indicate that VR has a positive effect on alleviating pain and reducing anxiety in pediatric patients with burn injuries.Systematic Review RegistrationPROSPERO (CRD420251058930).